Analisis Kesulitan Belajar Matematika Siswa Kelas III SD Negeri Mranak 01 Demak - Nurul Qomariyah; Rahmat Rais; Aries Tika Damayani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The background that prompted this research was that students still found difficulties in solving fraction problems in mathematics in class III on fractional arithmetic operations. The problem in this study is what are the learning difficulties experienced by students in class III SD N Mranak 01 Demak in completing fractional arithmetic operations and what factors cause students to experience learning difficulties in fractional operations in class III students at SD N Mranak 01 Demak. The purpose of this study was to find out what difficulties students experienced in solving fractional problems in class III SD N Mranak 01 Demak. This type of research is descriptive qualitative. Using test methods, observation, interviews, questionnaires and documentation. The subjects of this study were class III students at SD N Mranak 01 Demak. It can be concluded that the results of this study were 26 students in class III SD N Mranak 01 Demak, who experienced learning difficulties in fractional material totaling 8 students.